Looming crisis – changing climatic conditions in Ghana's breadbasket: the experiences of agrarian migrants. Issue 4 (19th May 2021) - Baada, Jemima Nomunume; Baruah, Bipasha; Luginaah, Isaac
ABSTRACT: Climate change disproportionately affects livelihoods of poor and vulnerable people. The Upper West Region of Ghana is a climate-affected area where agrarian livelihoods have become unsustainable, with migration to the Brong-Ahafo Region (BAR) becoming a key adaptation strategy. There is little research on postmigration experiences in BAR. Using qualitative methods, this article explores migrant farmers' premigration expectations and postmigration experiences. The findings reveal that BAR is also experiencing environmental degradation, which makes farming less profitable. The study highlights the benefits and disadvantages of agrarian migration as a response to climate change, and the need for proactive policy action regarding climate change.